BEHAVIOR OF CADMIUM AND OTHER INDICATORS IN SOIL AND ALMONDS OF COCOA (Theobroma cacao L.), UNDER APPLICATION OF COMPOST AND NPK - FLORIDA ROFNER, Nelino (2018)
In the last decade, research warns of high levels of cadmium (Cd2+) in soils and almonds in certain areas of Peru. Also, the relationship that Cd2+ presents with some physical and chemical soil indicators. Therefore, the objective was to evaluate the effect of compost and NPK on the Cd2+ of the soil, almonds and the relationship with other soil indicators, in a cocoa plantation CCN-51 (Theobroma cacao L.) in the Padre Abad province, region Ucayali-Peru. The research used a completely randomized block design (DBCA) with four treatments and four repetitions, where T1: control treatment, T2: compost at a rate of 3,000 Kg.ha-1, T3: NPK at a dose of 84-35-161 , and T4 compost at a rate of 1500 kg.ha-1 + NPK 42-18-80; was evaluated Cd2+ available from the soil,  and in almonds, % clay, organic matter (MO), pH and Cation exchange capacity (CICe). The results show means between 18.5 to 22% of clay, 4.11 to 4.42 of pH, 2.32 to 4.41% of MO, 7.87 to 9.45 Cmol / kg of CICe, 0.17 to 0.23 μg. g-1 of Cd2+ in the soil and 0.31 to 0.43 μg. g-1 in almonds. A significant positive correlation was found between the treatments and the pH, MO and Cd2+ indicators in almonds and significant negative for CICe. It is concluded that the application of compost and NPK had a significant effect on the pH, MO, CICe and Cd2+ indicators in almonds; finding significant correlation between CICe, MO, and Cd2+ in almond, between Mg2+ and Cd2+ in soil and highly significant between CICe and Cd2+ in soil. Being, T2 (compost) the treatment with lower values of Cd2+ in soil and almonds.